Toward a Trustworthy and Interoperable Metaverse: A Systematic Review of Blockchain-Based Enhancements - Naseef, Muhammed Abdulkhaliq; Shakir, Ahmed Chalak (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
The integration of blockchain technology with the metaverse has the potential to revolutionize online interaction by enabling secure, trustworthy, and interoperable virtual environments. This systematic literature review (SLR) explores how blockchain technologies can address fundamental challenges within the metaverse, particularly concerning security, trust, and interoperability. Eighteen research articles published between 2020 and 2025 were examined from top academic databases and grouped into three main topics: security methods using blockchain, systems for decentralized trust, and protocols for working across different platforms. The results show that blockchain’s decentralization, immutability, and cryptographic foundations enable robust authentication, secure data exchange, and trustless identity systems. Additionally, blockchain facilitates seamless integration between diverse metaverse platforms through smart contracts, cross-chain protocols, and tokenized assets. Despite significant promise, challenges such as computational overhead, real-world deployment limitations, and lack of standardization persist. This review offers a consolidated foundation for ongoing research and proposes directions for integrating blockchain into scalable and reliable metaverse ecosystems.